2016
DOI: 10.1083/jcb.201606081
|View full text |Cite
|
Sign up to set email alerts
|

GTSE1 tunes microtubule stability for chromosome alignment and segregation by inhibiting the microtubule depolymerase MCAK

Abstract: The microtubule depolymerase MCAK influences chromosomal instability (CIN), but what controls its activity remains unclear. Bendre et al. show that GTSE1, a protein found overexpressed in tumors, regulates microtubule stability and chromosome alignment during mitosis by inhibiting MCAK. High levels of GTSE1 are linked to chromosome missegregation and CIN.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(94 citation statements)
references
References 71 publications
(132 reference statements)
11
81
0
Order By: Relevance
“…Another potential functional member of the CHC/TACC3 complex is GTSE1 (pronounced jitsee one; Monte et al, 2000), an intrinsically disordered protein that has been shown by proteomic analysis to interact with the CHC/TACC3 complex in cells (Hubner et al, 2010). Two recent studies showed that GTSE1 localizes to the spindle during mitosis and, like TACC3, is necessary for astral MT stabilization and efficient chromosome alignment (Bendre et al, 2016;Tipton et al, 2017). We showed that GTSE1 stabilizes MTs in mitosis by inhibiting MCAK activity (Bendre et al, 2016).…”
Section: Introductionmentioning
confidence: 76%
“…Another potential functional member of the CHC/TACC3 complex is GTSE1 (pronounced jitsee one; Monte et al, 2000), an intrinsically disordered protein that has been shown by proteomic analysis to interact with the CHC/TACC3 complex in cells (Hubner et al, 2010). Two recent studies showed that GTSE1 localizes to the spindle during mitosis and, like TACC3, is necessary for astral MT stabilization and efficient chromosome alignment (Bendre et al, 2016;Tipton et al, 2017). We showed that GTSE1 stabilizes MTs in mitosis by inhibiting MCAK activity (Bendre et al, 2016).…”
Section: Introductionmentioning
confidence: 76%
“…Abnormal kinetochore‐microtubule attachment leads to the production of aneuploid cells . A decrease or loss of KIF2C expression level will result in an abnormal alignment of chromosomes in the S phase of mitosis and a faulty separation of chromosomes in the G2 phase, which will disrupt the normal mitotic process . All these are considered to be the potential causes of tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…6 A decrease or loss of KIF2C expression level will result in an abnormal alignment of chromosomes in the S phase of mitosis and a faulty separation of chromosomes in the G2 phase, which will disrupt the normal mitotic process. 7 All these are considered to be the potential causes of tumorigenesis. Factually, the role of KIF2C in many cancers such as tongue cancer, colorectal cancer, breast cancer, and so on has been reported previously.…”
mentioning
confidence: 99%
“…This, in turn, causes cancer cells to frequently gain or lose chromosomes, a phenomenon known as chromosome instability (CIN) (1, 2). reveal that microtubule hyperstabilization and CIN may be driven, in part, by the overexpression of a protein called GTSE1, which inhibits the microtubule depolymerase MCAK (3).…”
mentioning
confidence: 99%
“…In interphase cells, GTSE1 promotes cell migration by binding to the microtubule plus end tracking protein EB1 (4), but, during mitosis, the protein is recruited to the spindle by a protein called TACC3 (5). What, if anything, GTSE1 does at the spindle is unknown, however, so Alex Bird and colleagues at the Max Planck Institute of Molecular Physiology in Dortmund, Germany, decided to deplete the protein from U2OS cancer cells (3). “We saw that essentially all the different microtubule populations within the spindle were destabilized in the absence of GTSE1,” Bird explains.…”
mentioning
confidence: 99%